An opportunity lost the Truman administration and the farm policy debate - Dean, Virgil W. (University of Missouri Press, 2006)
"Examines Charles Brannan's agricultural plan, the farm policy debate, and Harry S. Truman's quest for a long-range agricultural program. Assesses Truman's relationships with farmers and with politicians and the search for a workable peacetime program, especially as it related to the parity price foundation and price supports"--Provided by publisher.